Education and Training on Introduction of Geology for Spatial Planning - Iwan Fahlevi; Agus Sutanto; Andiani Andiani; Saut Aritua Hasiholan Sagala; Sulamith Kastl (The Indonesian Journal of Planning and Development, 2018)
In 2015 and 2016, the Education and Training Center of Geology, Mineral, and Coal (Pusdiklat Geologi, Mineral dan Batubara) developed training of Introduction to Geology for Spatial Planning based on a new standard curriculum. The objective of this training is to prepare the participants in dealing with basic environmental geology data and its analysis for spatial planning, including data and information management and generation, basic knowledge in the geographic information system (GIS) as well as the data interpretation and obstacles within spatial planning regarding the geological factors. Furthermore, the training is meant to introduce participants to basic methods in spatial planning processes, such as participatory planning, scenario building, and conflict analysis for geologically-induced conflicts in spatial planning.  One focus of the training is the issue of disaster prevention via spatial planning. For this topic, the training refers to the Guideline for the Implementation of Geological Hazard Information in Spatial Planning (Pedoman Penyusunan Informasi Bahaya Geologi untuk Penataan Ruang) developed by the Geological Agency of Indonesia in 2015, supported by the German Development Cooperation. The approach of the new training differs from the previous standard curriculum which focused on operational and more technical procedures and scoring of geological analysis. One problem of passed training is the effectiveness of the training due to different knowledge levels of the participants, outsourced training parts and the often-passive didactic method implemented during the training. The new training is using a blended learning system, combining between e-learning in the introductory phase of the training to harmonize the participant's background and a highly interactive approach with practical elements to encourage the participants to apply theoretical knowledge directly. Moreover, the training aims to improve the participants’ capabilities to implement their knowledge to real case studies, from which they are likely to become more competent to fulfill their office tasks for sure. The new curriculum and training setup is adaptive to the current development process, using methods of gap analysis and SWOT analysis, determined contents, didactical needs, and limitations. These methods help to compare the expected performance of the new curriculum, both internally and externally, with the performance of the previous curriculum. Furthermore, the whole process is accompanied by focus group discussions to acquire feedback, reviews, and considerations for the setup and content of the changes applied to the curriculum.